2016
DOI: 10.20286/jeslm-030282
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationship between Communication Skills and Mental Health and Job Empowerment

Abstract: A B S T R A C TThe aim of this study is to investigate the relation of communication skills with mental health and job empowerment of Melli Bank of Bandar Abbas in 2005. The study population includes 560 subjects. The sample size is selected using Cochran formula, which is equal to 142 subjects. The research sample is selected randomly. Research required data are collected using field method. Spreitzer Psychological Empowerment Questionnaire (1990), Mental Health Questionnaire (SCL 90 R) and Communication Skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…[ 1 ] Also, research has indicated that good communication and inter-personal skills play an effective role in preventing and decreasing the incidence of behavioral abnormalities and mental disorders, reducing drug abuse, preventing violent behaviors, strengthening self-reliance, improving skills to deal with pressures and stresses, and establishing optimal social relationships. [ 1 12 ] Poor communication skills and inefficient emotional, psychological, and social abilities, especially in the family, make people vulnerable and expose them to a variety of mental, social, and behavioral disorders. [ 13 ] Awareness of these patterns and communication skills safeguards a person from danger in critical life situations, preventing from all kinds of mental–physical problems, psychological disturbances, personal depression, anxiety, and distress by facilitating the adaptability to the surrounding environment and arrangement of daily interactions, which enable a person to overcome mental stress.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Also, research has indicated that good communication and inter-personal skills play an effective role in preventing and decreasing the incidence of behavioral abnormalities and mental disorders, reducing drug abuse, preventing violent behaviors, strengthening self-reliance, improving skills to deal with pressures and stresses, and establishing optimal social relationships. [ 1 12 ] Poor communication skills and inefficient emotional, psychological, and social abilities, especially in the family, make people vulnerable and expose them to a variety of mental, social, and behavioral disorders. [ 13 ] Awareness of these patterns and communication skills safeguards a person from danger in critical life situations, preventing from all kinds of mental–physical problems, psychological disturbances, personal depression, anxiety, and distress by facilitating the adaptability to the surrounding environment and arrangement of daily interactions, which enable a person to overcome mental stress.…”
Section: Introductionmentioning
confidence: 99%